Superconducting gap induced barrier enhancement in a BiFeO3-based heterostructure - Lu, C. L. (2011)
We report the synthesis and characterization of an epitaxial heterostructure composed of multiferroic BiFeO3 and superconducting YBa2Cu3O7−δ thin films grown on (001) SrTiO3. Both the superconductivity of YBa2Cu3O7−δ and the erroelectricity of BiFeO3 are retained in the heterostructure. Current density-electric field characteristics measured from 30 to 170 K suggest a Schottky-emission-like transport at the BiFeO3 /YBa2Cu3O7−δ interface. Furthermore, the temperature dependence of the barrier height shows an anomalous enhancement at TC, indicating an intimate coupling between the multiferroic and the superconducting layers.